Estudo 3-D do impacto da geometria dos dutos sobre o escoamento do ar no leito poroso em secadores de fluxo misto - Jungbeck, Marcelo Roberto (2023)
This work aims to evaluate the effect of the geometry and arrangement of the air ducts in mixed flow dryers, using Computational Fluid Dynamics (CFD) as an analysis tool. The focus was on the air distribution in the porous bed and the pressure drop of the system, which are important factors for the performance of the drying process. Twelve different models were analyzed, varying the inclination of the ducts (50 and 60°), the horizontal distribution of the ducts (3, 4 and 6 ducts) and the cross sections of the ducts (constant and variable). All models maintained the same volume of grains and the same specific air flow rate. The validation of the approach for porous media and the mesh used was performed by constructing a CFD model that replicated the practical study carried out by Scaar et al. (2016) Scaar et al. (2016). The results of the CFD model were compared to the practical results, demonstrating the validity of the methodology and the mesh selected. The simulations of the 12 models showed that the design configuration in drying equipment significantly affects the pressure drop and the uniformity of air distribution. It was found that increasing the number of ducts, resulting in smaller and closer ducts, reduced pressure losses and provided good uniformity in air distribution. The inlet section of the ducts, which influences the inlet air velocity, also proved to be relevant in equipment design. Wider sections decreased air velocity, resulting in lower pressure drop and better uniformity in air distribution. In addition, variation in duct section contributed to uniformity of air distribution. On the other hand, no direct relationship was observed between duct inclination angle, pressure drop and uniformity of air distribution.